A Bibliometric Analysis of the Application of Biomimicry in Water Conservation - Loso Judijanto; Abdul Muiz (Westscience Press, 2026)
This study conducts a bibliometric analysis of research on the application of biomimicry in water conservation to map its intellectual structure, thematic evolution, and global collaboration patterns. Data were retrieved from a selected scientific database and analyzed using bibliometric techniques, including co-occurrence analysis, co-authorship mapping, and density visualization. The findings reveal that biomimicry serves as a central interdisciplinary framework connecting materials science, environmental engineering, and sustainability studies. Keyword analysis identifies surface science concepts such as hydrophobicity, wettability, and contact angle as the foundational knowledge base, while applied themes including water filtration, membranes, and water treatment represent the primary technological focus. Overlay visualization indicates a temporal shift from fundamental physicochemical studies toward application-driven research in sustainable water management and biomimetic materials. Network analysis further demonstrates a highly collaborative global research structure dominated by leading countries such as the United States and China, alongside contributions from Europe and emerging economies, though with uneven participation levels.